Family ethnicity: strenght in diversity - McAdoo, Harriette Pipes ed. (California: Sage Publications, Inc., 1993)
Contents : Family ethnic diversity,family ethnicity in america,african american families,mexican and spanish-origin american families,native american families,muslim families,asian american families,practice with ethnic families.
Includes bibliographical references and index
Keywords: Familia - Condiciones sociales